Intelligent TNVR Ear-Tag Recognition and Monitoring System for Stray Animal Management - Zhi-Yu Wang; Yung-Hoh Sheu; Bo-Kai Yang; Chi-Jen Chen; Chi-Wen Chen (International Journal of Engineering and Technology Innovation, 2026)
This study aims to enhance stray animal management by improving the efficiency and sustainability of the trap-neuter-vaccinate-return (TNVR) process. An intelligent monitoring system integrating image recognition and radar sensing is proposed for real-time detection and identification. The system utilizes a domain-specific ear-tag recognition model based on OpenCV preprocessing and YOLOv8, achieving an accuracy of 91% under various environmental conditions. Captured data are automatically uploaded via 4G to a centralized server, supporting continuous monitoring and instant alerts. Designed for high-density urban settings, the system mitigates manual workload and enhances decision-making efficiency, contributing to sustainable and humane stray animal control. Although the proposed system demonstrates high detection accuracy and robust performance under real-world conditions, the current evaluation is conducted on a moderate-scale dataset; future work will focus on large-scale deployment and cross-context validation to further examine system generalizability.